The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00436-013-3337-z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue tropism of Toxoplasma gondii in turkeys (Meleagris gallopavo) after parenteral infection

Abstract: Turkeys are known to be natural hosts for the zoonotic protozoan parasite Toxoplasma gondii. The objective of the present study was to gain further knowledge of possible predilection sites of T. gondii infection in this species after parenteral application of tachyzoites. A total of 38 turkeys were infected with different doses of T. gondii tachyzoites. Birds were killed either 6 to 8 or 10 to 12 weeks after the experimental infection. Fourteen different tissues per bird were investigated by a nested polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…A positive control consisting of DNA from cell culture-derived ME49 tachyzoites and a negative control (aliquot of currently used DNA elution buffer) were carried along in every PCR batch. The PCR reaction was performed as a direct PCR followed by a nested PCR as described by Zöller et al (2013). The mastermix for a direct PCR reaction with 25 μ L contained 0·5 U GoTaq ® Flexi Polymerase and 1×GoTaq ® Flexi Buffer (Promega GmbH, Mannheim, Germany), 200 μ m of each dNTP (Fermentas, St. Leon Rot, Germany), 3 m m MgCl 2 , 0·4 μ m of each primer Tg1 (5′-AAA AAT GTG GGA ATG AAA GAG-3′) and Tg2 (5′-ACG AAT CAA CGG AAC TGT AAT-3′).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive control consisting of DNA from cell culture-derived ME49 tachyzoites and a negative control (aliquot of currently used DNA elution buffer) were carried along in every PCR batch. The PCR reaction was performed as a direct PCR followed by a nested PCR as described by Zöller et al (2013). The mastermix for a direct PCR reaction with 25 μ L contained 0·5 U GoTaq ® Flexi Polymerase and 1×GoTaq ® Flexi Buffer (Promega GmbH, Mannheim, Germany), 200 μ m of each dNTP (Fermentas, St. Leon Rot, Germany), 3 m m MgCl 2 , 0·4 μ m of each primer Tg1 (5′-AAA AAT GTG GGA ATG AAA GAG-3′) and Tg2 (5′-ACG AAT CAA CGG AAC TGT AAT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Fowl is considered to be one of the most important intermediate hosts in the life cycle of T. gondii (Dubey, 2010 b ), but little is known about the duration of persistence of T. gondii in tissue of poultry. Zöller et al (2013) demonstrated a persistence of T. gondii in turkeys over a period of 12 weeks but to our knowledge the persistence of T. gondii in chicken has not been investigated. There is little information as to whether chickens are able to eliminate a T. gondii infection, as has been observed for some of the other intermediate host species (Beverley et al 1977).…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, T . gondii infection is prevalent in many domestic and wild avian species, although the epidemiological role of those species is poorly understood [ 1 , 5 , 7 , 8 , 9 ]. Birds are suspected to act as dispersive agents of T .…”
Section: Introductionmentioning
confidence: 99%
“…A study on pigs sacrificed at 76 dpi19 showed 3/6 positive liver samples. Zöller et al showed, on 30 turkeys sacrificed 6–12 weeks after intravenous injection of tachyzoïtes,20 that liver and breast muscle were the most infected organs, with Toxoplasma DNA detection in 43.3% and 26.7% of samples, respectively.…”
Section: Discussionmentioning
confidence: 99%